2018
DOI: 10.1016/j.ridd.2018.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Children with autism and attention deficit hyperactivity disorder. Relationships between symptoms and executive function, theory of mind, and behavioral problems

Abstract: Title Children with autism spectrum disorder and comorbid attention deficit hyperactivity disorder. Relationships between symptoms and executive function, social cognition, and behavioral problems

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0
16

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 49 publications
3
36
0
16
Order By: Relevance
“…However, compared with typically developing children, relatively less attention has been directed to the study of PA in children with ADHD/ASD. Given that previous studies in typically developing children generally reported PA benefits EF and MS, especially in inhibitory control (Berenguer et al, 2018) and gross motor development (Wrotniak et al, 2006;Lopes et al, 2011), PA has the potential to be used as a strategy to improve EF and MS in children with ADHD/ASD.…”
Section: Introductionmentioning
confidence: 99%
“…However, compared with typically developing children, relatively less attention has been directed to the study of PA in children with ADHD/ASD. Given that previous studies in typically developing children generally reported PA benefits EF and MS, especially in inhibitory control (Berenguer et al, 2018) and gross motor development (Wrotniak et al, 2006;Lopes et al, 2011), PA has the potential to be used as a strategy to improve EF and MS in children with ADHD/ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Episodic memory helps individuals to maintain goals and task rules and is thought to be impaired in ASD [Ben Shalom, 2003; Bowler, Gaigg, & Lind, 2011]. Finally, ADHD symptoms can exacerbate EC problems in autistic persons [Berenguer, Rosello, Colomer, Baixauli, & Miranda, 2018].…”
Section: Introductionmentioning
confidence: 99%
“…Beide Störungen verbessern sich meist im Laufe des Lebens durch optimierte Kompensationsleistungen, sind jedoch meist auch im Erwachsenenalter mit signifikanten Einbußen in der Lebensqualität assoziiert und können zu erheblichen Schwierigkeiten in beruflichen, familiären und sozialen Bereichen führen. Symptomatisch finden sich ebenso Überschneidungen hinsichtlich Aufmerksamkeitsstörung, Reizüberflutung und Ablenkbarkeit, interaktionellen Schwierigkeiten mit Peers, Schwierigkeiten in der sozialen Kognition, Unruhe und impulsivem Verhalten, Defiziten in den Exekutivfunktionen und der Theory of Mind (TOM) [71][72][73][74][75][76].…”
Section: Differenzialdiagnostische Unterschiedeunclassified
“…Während bei ASS Einschränkungen in der reziproken Kommunikation und Interaktion charakteristische Merkmale der Störung sind, die auf ein "Kerndefizit" zurückgeführt werden, so wird dies bei ADHS häufig als Folge der Unaufmerksamkeit und der Ablenkbarkeit angesehen. Dennoch scheint es auch bei von ADHS Betroffenen Einschränkungen in affektiven Verarbeitungsprozessen und der ToM zu geben, wobei die Unterscheidung was ursächlich an den berichteten sozialen Einschränkungen beteiligt ist, klinisch teilweise herausfordernd ist [54,72,80]. Liegen beide Störungen gleichzeitig vor, so sind diese Fähigkeiten ausgeprägter eingeschränkt.…”
Section: Differenzialdiagnostische Unterschiedeunclassified